Methods for the Estimates of Regional Economic Structures - Šafr, Karel; Sixta, Jaroslav (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper brings an overview of statistical methods used for estimation of regional economic structures. The methods are presented using the case of the Czech Republic and Czech regional Input-Output tables for 2013. Several models used and derived for these purposes are presented within the paper, and their results are subjected to sensitivity analysis with the aid of the CGE model. Regional economic structures are necessary for advanced economic analyses aimed at the regional level, and since they are not published by official statistical agencies, they must be based on academic research. The core of regional structures is derived from both national and regional Input-Output tables and, therefore, they provide a good basis for the use of Input-Output analysis. From the statistical point of view, computational process results in a big square matrix depicting the flows of products allowing the use of dynamic Input-Output models. There can be found several methods for obtaining the flows between the regions and we briely focus on gravity method, optimalization of distance, physical flows and distance betweem the centroids. The results presented within the paper should be useful for economists dealing with regional economic models
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 401-418
Keywords: regional Input-Output; interregional flows; computable general equilibrium